Frequency of the CCR5-delta32 allele in Brazilian populations: A systematic literature review and meta-analysis. - Silva-Carvalho, Wlisses Henrique Veloso; De Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Crovella, Sergio; Guimarães, Rafael Lima (Infect Genet Evol, 2016)
The CCR5 is a chemokine receptor widely expressed by several immune cells that are engaged in inflammatory responses. Some populations have individuals exhibiting a 32bp deletion in the CCR5 gene (CCR5-delta32) that produces a truncated non-functional protein not expressed on the cell surface. This polymorphism, known to be associated with susceptibility to infectious and inflammatory diseases, such as osteomyelitis, pre-eclampsia, systemic lupus erythematous, juvenile idiopathic arthritis, rheumatoid arthritis and HIV/AIDS, is more commonly found in European populations with average frequency of 10%. However, it is also possible to observe a significant frequency in other world populations, such as the Brazilian one. We performed a systematic review and meta-analysis of CCR5-delta32 genetic association studies in Brazilian populations throughout the country to estimate the frequency of this polymorphism. We also compared CCR5-delta32 frequencies across Brazilian regions. The systematic literature reviewed studies involving delta32 allele in Brazilian populations published from 1995 to 2015. Among the reviewed literature, 25 studies including 30 Brazilian populations distributed between the North, Northeast, South and Southeast regions were included in our meta-analysis. We observed an overall allelic frequency of 4% (95%-CI, 0.03-0.05), that was considered moderate and, notably, higher than some European populations, such as Cyprus (2.8%), Italy (3%) and Greece (2.4%). Regarding the regional frequency comparisons between North-Northeast (N-NE) and South-Southeast (S-SE) regions, we observed an allelic frequency of 3% (95%-CI, 0.02-0.04) and 4% (95%-CI, 0.03-0.05), respectively. The populations from S-SE regions had a slightly higher CCR5-delta32 frequency than N-NE regions (OR=1.41, p=0.002). Although there are several studies about the CCR5-delta32 polymorphism and its effect on the immune response of some infectious diseases, this report is the first meta-analysis study that provides a descriptive study of the distribution of CCR5-delta32 allele in Brazilian population.